DAMPAK BANJIR TERHADAP PENDAPATAN USAHATANI PADI SAWAH DESA SIMPANG KIRI KECAMATAN TENGGULUN KABUPATEN ACEH TAMIANG - Nurul Abdaini; Rozalina, Rozalina; Silvia Anzitha (Bajang Institute, 2024)
This study aims to analyze the level of difference in rice farming income caused by flooding which is one of the problems often experienced by farmers in Simpang Kiri Village, Tenggulun District, Aceh Tamiang Regency. With this flood, it can have an impact on production costs so that it has an impact on production and farmers' income. The method used is a quantitative descriptive method , namely researchby describing the situation in the field from a number of individuals who are intervieweddirectly, who as a sample. Analysis used Sample idenpendent test (T-test). The results of the studyshowed that the average income/rice farming before the flood in Simpang Kiri Village, Tenggulun District, Aceh Tamiang Regency was Rp 10.495.000 /UT/MT with an average rice income of Rp 26.910.000 /Ha. while the average income/farming after the flood was Rp 5.001.000 /UT/MT with an average income of Rp 12.822.000/Ha.